Hemşirelik Mesleksel Beceri Laboratuarındaki Psikomotor Beceri Eğitiminin Öğrenci ve Eğiticiler Tarafından Değerlendirilmesi. - METE, Samiye; UYSAL, Nurcan (Turkish Journal of Research & Development in Nursing / Hemşirelikte Araştırma Geliştirme Dergisi, 2010)
Objective: The aim of this study was to determine the opinions of students and instructors about the psychomotor skill training applied by using skill lists, reasons of skill steps, videos, and scenarios. Method: A total of 82 second-grade students, who studied at an University in a province in Aegean Region, School of Nursing in the 2007-2008 academic year, and 15 instructors, who attended the studies of professional skill laboratory of this class, were included in the study. The skill training was applied by using laboratory scenarios, skill lists and videos, in which four different subjects were discussed. The data were collected with "Professional Skills Feedback Form" which was prepared by the instructors. This form consists of total 12 items including planning, application, and learning subtitles. Each item is evaluated between 0=Very poor and 4=Very good scores. The evaluations were performed by calculating the mean scores of each item. Results: The mean scores of the students and instructors were as follows, respectively: 3.75, 3.40 for the order receive and oral local drug application; 3.85, 3.22 for applying the protective position; 3.86, 3.72 for the application of intravenous, intramuscular and subcutaneous injection; 3.89, 3.52 for the application of intravenous fluid therapy. Students noted that the laboratory studies were amusing, maintaining permanent learning and increasing the problem solving skills. The feedbacks of instructors also supported the positive feedbacks of students. Conclusion: It was determined that different methods used in laboratory studies facilitated learning of the students and provided interest and motivation. Studying on methods that provide students to attend the laboratory with theoretical preparation was suggested.